The implementation of the socio-drama learning method at MTsN 2 Malang - H. Hidajati; Nur Wahyu Rochmadi; Siti Awaliyah (Inovasi Kurikulum)
An appropriate teaching method can facilitate the achievement of learning objectives. This study examined students' sense of responsibility and learning outcomes by implementing the Socio-drama method in Pancasila and Citizenship Education. Socio-drama is a learning approach that involves students interacting with their peers in class, where they role-play and dramatize characters according to the roles assigned. This research employed classroom action research based on Kurt Lewin's action research procedures. The study was conducted in two cycles, with the first cycle showing that students' sense of responsibility and learning outcomes still below the mastery standard, prompting the continuation of the second cycle. In the second cycle, results improved, so a percentage of scores obtained the findings indicate that the Socio-drama method is highly effective in improving students' sense of responsibility and learning outcomes. Therefore, the socio-drama method can be recommended as a practical approach to teaching citizenship education.